Effects of maggot antimicrobial peptides on growth performance, immune function, and cecal flora of yellow-feathered broilers - Gao, Shengjie; Zhang, Quancheng; Liu, Caixia; Shen, Hong; Wang, Jungang (Frontiers in Veterinary Science, 2023)
This study investigated the effects of maggot antimicrobial peptides on growth performance, blood parameters, immune organ index, and cecum microbial diversity in yellow broilers. The addition of 100-300 mg/kg maggots antimicrobial peptides to the corn-soybean meal basal diet was evaluated. Two hundred and forty one-day-old yellow-feathered broilers were randomly divided into four groups (60 chickens in each group): basal diet group (BC group), basal diet group + 100, 200, 300 mg/kg maggots antimicrobial peptides (MDAL group, MDAM group, and MDAH group).The result showed that the average daily feed intake (ADFI) of the BC group, MDAM group, and MDAH group was higher than that of the MDAL group (P > 0.05), the average daily gain of MDAM group and MDAH group was significantly higher than that of BC group and MDAL group (P < 0.05), but the feed-weight ratio (F/G) was significantly lower than that of BC group (P < 0.05). The total protein (TP) content in the MDAM group and MDAH group was significantly higher than that in the BC group (P < 0.05), and the albumin (ALB) content in the MDAH group was higher than that in the BC group (P > 0.05). The contents of IgA and IgG in the MDAH group were significantly higher than those in the BC group (P < 0.05). In contrast, the content of alanine aminotransferase (ALT) in the MDAH group was significantly lower than that in the BC group (P < 0.05). The thymus and spleen indexes of the MDAH group were significantly higher than those of the BC group (P < 0.05). 16S rDNA sequencing results showed that Bacteroidota and Bacteroides were the dominant phylum and genus of cecal microorganisms at the phylum and genus levels, respectively. Cecum microorganisms are mainly involved in biological processes such as energy production and conversion, amino acid transport and metabolism, and carbohydrate transport and metabolism. It was concluded that adding different doses of maggot antimicrobial peptide to the basal diet could improve yellow-feathered broilers' growth and immune performance and change the cecum flora. The appropriate dose of antimicrobial peptide addition was 300 mg/kg.